ASSESSMENT OF SOME ABIOTIC FACTORS ON MICROBIAL BIOPRODUCTS USEFUL IN BIOCONTROL OF PHYTOPATHOGENS - Fendrihan, Sergiu; Dinu, Sorina; Sicuia, Oana Alina; Constantinescu, Florica (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
The environmental factors may influence the growth of microorganisms, by favoring their growth or slowing their multiplication rate and the synthesis of different metabolites. Parameters such as temperature, aeration, nutrients, pH or tolerance to NaCl can become limiting factors for microorganisms survival. Bacillus subtilis and related species can grow in variable pH conditions, maintaining the cytoplasmically pH in a relatively close range, stable to the synthesis of proteins and nucleic acids.The aim of this work was to assess the influence of some abiotic factors on the biocontrol activity of microbial bioproducts, based on beneficial strains from Bacillus sp.. The bioproducts were tested in vitro against soil borne fungi at different temperatures and pH conditions. The results showed that the antagonistic activity of the biopreparates, tested at 27Â°C and 25Â°C, against phytopathogenic fungi released antifungal metabolites which inhibited the fungal growth. Also, when different pH values were analyzed, the results reflected that at pH 5.5 and pH 8.5 the bioproducts maintained the same antagonistic effect as in the control variant (pH 7.0).